Synthesis in water-free DMF, characterization, electrical, and gas sensing properties of bis[2-(2-aminoethylamino)ethanol]copper(II) dibromide - YALÇIN, BAHATTİN; KAKI, ESRA HACER; DUMLUDAĞ, FATİH (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
2-(2-Aminoethylamino)ethanol (L) reacts with cupric bromide in dimethylformamide to give a mononuclear complex of Cu(II) [L2Cu]Br-2, with six-coordinate distorted octahedral geometry, in which two molecules of tridentate (N,N,O) ligand are involved. The structure was confirmed by spectroscopic methods, elemental and thermogravimetric analyses, and magnetic measurements. Optimization of possible configurations indicated the formation of the trans structure of the complex. Experimental results indicate that the investigated complex, bis[2-(2-aminoethylamino)ethanol] copper(II) bromide, behaves as a semiconductor in the studied temperature range of 298-388 K. Gas sensing properties of the film for the volatile organic compounds (VOCs): acetone, tetra-chloromethane, chloroform, ethanol, and methanol, were also investigated as a function of vapor concentration and temperature in dark. The film showed maximum sensitivity to tetrachloromethane and ethanol vapors at room temperature. Responses of the film to the tested gases are reversible.
Keywords: 2-(2-aminoethylamino)ethanol; copper(II) bromide; six coordinated Cu(II) complex; semiconductor; gas sensing; COPPER PHTHALOCYANINE; METAL-COMPLEXES; THIN-FILMS; CONDUCTIVITY; DIOXIDE